Microclimatic Factors of Blacktop Roads as they Affect Bird Behavior, Diurnal Distribution and Range - Whitford, Philip Clason (University of Wisconsin-Stevens Point, College of Natural Resources, 1976)
Between 11 May and 30 September 1974, 2127 birds were observed on the surface of blacktop roads. Relationships between the presence of birds on the road and air temperatures were evaluated against data from four microclimates: the road in the sun, the road in the shade, the litter layer under pines, and the ground layer in herbaceous vegetation. The presence of birds also was evaluated relative to varying cloud cover, wind velocity, precipitation, and dampness of the road surface. At the times when the maximum number of birds was present on the road surface, the temperature of the macadam road in the sun was significantly warmer than the ambient air temperature or the microclimates of the litter layer beneath the pines or the herbaceous ground layer. It appeared that the birds used the macadam roads for warmth. The existence of the man-made microclimate of the macadam road appeared to influence bird behavior, diurnal distribution, and possibly the northward distribution of some species.